Connectivity and network development of carbonate-hosted fault damage zones from western Malta. (December 2020) - Nixon, Casey W.; Nærland, Kari; Rotevatn, Atle; Dimmen, Vilde; Sanderson, David J.; Kristensen, Thomas B.
Abstract: Using outcrop-based examples, we investigate the topological and graph characteristics of various fault damage zones in carbonate rocks on Malta. The damage zone fracture networks are analysed as a series of nodes (isolated I- nodes; connected Y/X- nodes) and branches ( II-, IC-, CC- branches), which may link to form connected components and fracture-bounded regions. We compare the metrics of the different nodes, branches, regions and components that make-up each damage zone fracture network, calculating parameters that assess their connectivity. Results identify distinct topological signatures and graph metrics for different tip-, relay- and splay-damage zones, providing a new classification that describes and quantifies their arrangement and connectivity. Placing the studied damage zones in a fault evolutionary model highlights topological pathways whereby tip-damage zones, dominated by I- nodes and II- branches, give way to relay-damage zones, dominated by Y- nodes and CC- branches. During this process, tree-like components link to form larger interconnected components with many regions. This systematically changes the graph metrics of the network increasing the number of branches and regions relative to nodes and components. The topological pathways and graph metrics provide important insights into how damages zones might develop as faults propagate, interact and link and could have implications when assessing their importance for fluid-flow. Highlights: Describes topology and graph characteristics of fault damage zone fracture networks. Identifies distinct topological signatures and graph metrics for different fault damage zones. Quantifies spatial variations in fracture network properties within damage zones. I- nodes and II- branches dominate tip-damage zones whereas Y- nodes and IC- / CC- branches dominate relay-/splay-damage zones. Highlights topological pathways along which fault damage zones might evolve during fault propagation and linkage.